ASYMMETRY IN FARM-RETAIL PRICE TRANSMISSION: THE CASE OF CHILI INDUSTRY IN INDONESIA - Sahara Sahara; Bagus Wicaksena (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2013)
A decade of strong economic growth and rapid urbanization are transforming Indonesia’s food retail sector. In particular, supermarkets and related modern retail outlets are reorganizing how high value fruit and vegetable supply chains operate, effecting quantities, varieties, quality and prices. Among the agricultural development issues facing Indonesia’s policymakers are efficiency and distributional consequences of these transforming fruit and vegetable markets. This study examines asymmetric price transmission in chili supply chains to assess emerging market failures and potential equity implications for producers and consumers. The Indonesian government recognizes chilies as one of its 10 priority crops.  Chilies are produced by more than 400,000 small scale producers and are an essential ingredient in the Indonesian daily diet. Historically, chili markets have exhibited large price fluctuations in Indonesia. Two methods for examining asymmetric price transmission are compared using monthly data over an 18 year period in Java: Houck’s model and the Error Correction Model (ECM). Although commonly believed that modern retail sectors are increasing market power and influencing prices, both models suggest that there is no price asymmetry issue in the chili supply chain in Indonesia. Key word: chili, price, asimetric, transmission